PENGARUH PROFITABILITAS, FIRM SIZE, CURRENT RATIO, DEBT TO EQUITY RATIO TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013 – 2016 - Tamba, Sriayu; Sipangkar, Maria Betty; Siregar, Siti Aniva (Aksara Public, 2019)
The purpose of this study is to test and analyze the effect of profitability, firm size, current ratio, debt to equity ratio on stock prices in 2013-2016. The independent variables used in this study are profitability, firm size, current ratio, debt to equity ratio, while the dependent variable is the stock price. This study uses a quantitative approach, a type of descriptive research, the nature of research on causal relationships. The results of this study indicate partially the current ratio does not have a positive and insignificant effect on stock prices while profitability, firm size and the debt to equity ratio are parishly positive and significant effect on stock prices. Simultaneously profitability, firm size, current ratio and debt to equity ratio together have a significant and significant effect on the stock price variable. The results of the Adjusted R Square test 21.7% of the variation in stock prices can be explained by the four independent variables, namely profitability, firm size, current ratio and debt to equity ratio, while the remaining 78.3% is explained by other variables.